From malaria fighter to diabetes guardian: the emerging role of artesunate in treating diabetes and diabetic complications - Li, Dongze; Liang, Qingyue; Xu, Linghao; Zhang, Li; Gong, Qiming; Zhou, Tingting; Luo, Changfang; Huang, Wei; Yang, Yuan (Frontiers in Pharmacology, 2025)
Diabetes mellitus (DM) is a metabolic disease influenced by both genetic and environmental factors. The global incidence of DM is rising, and its multiple complications seriously affect patients’ quality of life and create a huge economic burden. At present, the prevention and treatment of DM mainly rely on oral or subcutaneous drugs, although oral drugs are more acceptable, they may produce more side effects and have limited effect on the treatment of diabetic complications. Artesunate (ART) is a first-line antimalarial drug widely used worldwide. Whether orally or intravenously, ART has high bioavailability and excellent pharmacokinetic properties in humans, and has shown good tolerance and safety in patients of multiple ages. Recent pharmacological studies have shown that, except for its antimalarial properties, ART also has a wide range of therapeutic potential for DM and its complications. This review aims to synthesize the latest research results, summarize and discuss the current role and mechanism of ART in improving diabetes and its complications, and provide a theoretical basis for the subsequent exploration of the anti-diabetes mechanism and the development of new antidiabetic agents based on ART, which has great clinical significance for strengthening the prevention and treatment effects of DM and its complications.